Increased tumour necrosis factor α production in mesenteric lymph nodes of cirrhotic patients with ascites. Issue 7 (1st July 2003) - Genescà, J; Martí, R; Rojo, F; Campos, F; Peribáñez, V; Gónzalez, A; Castells, L; Ruiz-Marcellán, C; Margarit, C; Esteban, R; Guardia, J; Segura, R
Abstract : Background: Cytokines produced in mesenteric lymph nodes of cirrhotic rats with bacterial translocation may participate in circulatory alterations of cirrhosis. Aim: To investigate whether cirrhotic patients present an increased local generation of cytokines in mesenteric lymph nodes. Methods: Mesenteric lymph nodes from 26 cirrhotic and 10 control patients were assessed for tumour necrosis factor α (TNF) and interleukin 6 mRNA and protein expression by competitive reverse transcription-polymerase chain reaction, and by enzyme immunoassay and immunohistochemistry, respectively. Results: Interleukin 6 levels were not different between cirrhotics and controls. Protein and mRNA TNF levels in mesenteric lymph nodes from cirrhotics were higher than in controls (p<0.05). Tissue expression of TNF by immunohistochemistry was more abundant in cirrhotics. Ascitic patients showed higher TNF levels (47 (34–54) pg/mg protein) than patients without ascites (18 (17–25) pg/mg protein) (p<0.001). Elevated TNF levels (>28 pg/mg protein) in cirrhotics were associated with a higher Child-Pugh score, the antecedent of ascites, a lower prothrombin rate, and higher bilirubin and blood TNF levels. The strongest association, confirmed by multivariate analysis, was with the presence of ascites (p<0.001). Bacterial infections after transplantation, mainly by enteric bacteria, were only detected in patients with high TNF levels in mesenteric lymph nodes (33% of patients; p=0.05). Conclusion: Patients with advanced liver cirrhosis, and especially with ascites, have increased local production of TNF in mesenteric lymph nodes that, in common with experimental cirrhosis, may also be induced by bacterial translocation.